Renal Expression of Light Chain Binding Proteins - Reiter, Thomas; Pajenda, Sahra; O'Connell, David; Lynch, Ciara; Kapps, Sebastian; Agis, Hermine; Schmidt, Alice; Wagner, Ludwig; Leung, Nelson; Winnicki, Wolfgang (Frontiers in Medicine, 2021)
Overproduction of human light chains (LCs) and immunoglobulins can result in various forms of renal disease such as cast nephropathy, monoclonal immunoglobulin deposition disease, LC proximal tubulopathy, AL amyloidosis, and crystal storing histiocytosis. This is caused by cellular uptake of LCs and overwhelmed intracellular transport and degradation in patients with high urine LC concentrations. LC kappa and lambda purification was evaluated by sodium dodecyl sulfate gel electrophoresis. LC and myeloma protein binding to immobilized renal proteins was measured by enzyme-linked immunosorbent assay (ELISA). The human protein microarray (HuProt™) was screened with purified kappa and lambda LC. Identified LC partners were subsequently analyzed in silico for renal expression sites using protein databases, Human Protein Atlas, UniProt, and Bgee. Binding of urinary LCs and immunoglobulins to immobilized whole renal proteins from 22 patients with myeloma or plasma cell dyscrasia was shown by ELISA. Forty lambda and 23 kappa interaction partners were identified from HuProt™ array screens, of which 21 were shared interactors. Among the total of 42 interactors, 12 represented cell surface proteins. Lambda binding signals were approximately 40% higher than kappa signals. LC interaction with renal cells and disease-causing pathologies are more complex than previously thought. It involves an extended spectrum of proteins expressed throughout the nephron, and their identification has been enabled by recently developed methods of protein analysis such as protein microarray screening. Further biochemical studies on interacting proteins are warranted to elucidate their clinical relevance.